EFFECT OF BAKING ON ANTIOXIDANT AND SENSORY ATTRIBUTES OF CURCUMIN ENCAPSULATES ENRICHED DESIGNER BREAD FORMULATIONS - H. Ashraf; M. S. Butt; M. Nadeem; A. Din (Journal of Animal and Plant Sciences, 2022)
Dietary intrusions emphasize on dynamic facets of phytonutrients due to strong antioxidant capacity. For the purpose, turmeric polyphenol i.e. curcumin was firstly extracted through conventional and supercritical extraction techniques following the preparation of microcapsule using maltodextrin and gelatin as enrobing material by freeze drying method. Afterwards, four types of designer bread weremade; turmeric (T1), microencapsulated nutraceuticalCSE (T2) and nutraceuticalSFE enriched breads (T3) along with control (T0). Physicochemical profile of resultant prototypes showed that addition of microencapsulated nutraceuticalSFE enhanced volume and phenolics from 572.60±7.56 to 686.20±8.25 cm3 and50.22±1.70 to 81.12±3.48 mg GAE/100g whilst hardness decreased from 2.97±0.11 to 3.36±0.10 kg/cm2 compared to control. Furthermore, hedonic response also improved with maximum scores for bread volume, crust color, symmetry and evenness in bake;8.01±0.39, 7.04±0.21, 3.83±0.16 and 1.94±0.05, respectively. Regarding internal parameters, highest scores for grain, crumb color, aroma, taste and texture were 12.32±0.38, 8.14±0.26,8.05±0.26, 16.41±0.61 and 13.02±0.52, correspondingly. Conclusively, microencapsulated nutraceuticalSFE enhances both antioxidant and sensorial profile of designer bread.
Keywords: turmeric; nutraceutical; microencapsulation; antioxidant; CSE and SFE